Compatibility of Trichoderma asperellum with Fungicides, Insecticides, Inorganic fertilizers and Bio-pesticides - Kumar, Theertha V; Veena, SS; Karthikeyan, S; Sreekumar, J (JOURNAL OF ROOT CROPS, 2017)
Trichoderma is one of the most common soil inhabitants and extensively studied bio-control agents in the management of plant pathogens. Species of Trichoderma are being used for the management of fungal diseases of tropical tuber crops. The diseases, collar rot of elephant foot yam, tuber rot of cassava, yam anthracnose and taro leaf blight could be managed by this bio-agent. Many a time in field, Trichoderma is applied along with agrochemicals. It makes essential to assess the compatibility of Trichoderma to these chemicals in order to tap the potential of them in the integrated management system. Present study was conducted in ICAR- CTCRI, Sreekariyam, Thiruvananthapuram to assess the compatibility of T. asperellum with commonly used fungicides, insecticides, fertilizers and cassava based bio- pesticides developed by ICAR-CTCRI. Thirteen fungicides, eight insecticides, three chemical fertilizers and two bio-pesticides were tested at different concentrations viz., 100ppm, 200ppm, 400ppm and 800ppm. Among the fungicides, Metalaxyl M + Mancozeb (Ridomil Gold) followed by Mancozeb (Indofil M-45) were least inhibitory to T. asperellum. The fungicides containing carbendazim (Saaf, Bavistin, Sprint, Turf, Starbenz) were highly inhibitory to the mycelial growth of Trichoderma even at the lowest concentration tested (100 ppm). Compared to fungicides, insecticides showed less toxicity to Trichoderma. Even at the highest concentration of 800 ppm, none of the insecticides could completely inhibit the mycelial growth of Trichoderma. The growth inhibition by the inorganic fertilizers were minimum exhibiting >10% mycelium growth inhibition at 800 ppm. The results of this study will help in choosing suitable chemicals in Integrated Disease Management (IDM) for tropical tuber crops